Палеогеографические особенности основных стоянок позднего палеолита бассейна реки Десны (Хотылево, Елисеевичи, Юдиново, Пушкари) - Грибченко, Ю.Н.; Куренкова, Е.И. (Археологический альманах, 2014)
Работа посвящена специфике освоения палеоландшафтов басейна Десны позднепалеолитическими сообществами людей. At the beginning of Late Valdai Glacial human communities actively populated Desna River basin. The earliest sites of Late Paleolithic are situated on watershed areas. The progressing cold snap and the formation of Periglacial landscapes did not correlate with intensive peopling of the central part of Eastern Europe. After the Last Glaciations Maximum the areas of human habitations sufficiently extended. The river valleys were occupied by the settlements with dwelling constructions. Large sites were placed on watersheds and on low terraces above the flood plain. Also, Late Paleolithic communities actively populated the territory of Desna basin in Late Glacial period. That times, the cultural layers of a number of settlements defined by the considerable densities of animal bones, tools and burnt bones, as well as bone dwellings. That is, the Late Glacial settlements characterized by long term occupational activities.